A Radical Democratic Lens to Rejuvenating European Union Democracy Support: Thinking about the Political with a Capital P. Issue 1 (1st June 2022) - Vandeputte, Nathan
Abstract: This article intervenes in the debates on reforming EU democracy support by offering a "radical reformist" approach. It departs from the observation that literature lacks a sustained theorization of reform which more effectively considers contestation as the very condition of democracy. As such, in contrast to withdrawing democracy from its contested nature, this article presents a theoretical argument, as informed by Chantal Mouffe's take on radical democracy, through which the EU more democratically can engage with and support the plurality of different contestations of democracy. In particular, a closer engagement with the radical democratic embrace of the political will allow for better reflection on how EU democracy support already is or can become democratic, empowering and receptive to the way democracy is understood locally.